Infrared Spectrum of the Adamantane+–Water Cation: Hydration‐Induced C−H Bond Activation and Free Internal Water Rotation. Issue 29 (4th June 2020) - George, Martin Andreas Robert; Förstel, Marko; Dopfer, Otto
Abstract: Diamondoid cations are reactive intermediates in their functionalization reactions in polar solution. Hydration is predicted to strongly activate their C−H bonds in initial proton abstraction reactions. To study the effects of microhydration on the properties of diamondoid cations, we characterize herein the prototypical monohydrated adamantane cation (C10 H16 + –H2 O, Ad + –W) in its ground electronic state by infrared photodissociation spectroscopy in the CH and OH stretch ranges and dispersion‐corrected density functional theory (DFT) calculations. The water (W) ligand binds to the acidic CH group of Jahn–Teller distorted Ad + via a strong CH⋅⋅⋅O ionic H‐bond supported by charge–dipole forces. Although W further enhances the acidity of this CH group along with a proton shift toward the solvent, the proton remains with Ad + in the monohydrate. We infer essentially free internal W rotation from rotational fine structure of the ν3 band of W, resulting from weak angular anisotropy of the Ad + –W potential. Abstract : C−H bond activation and free internal rotation: The infrared spectrum of the monohydrated adamantane cation reveals the hydration‐induced activation of its acidic C−H bond. Despite the strong CH⋅⋅⋅O ionic hydrogen bond in this prototypical reaction intermediate, the water ligand undergoes essentially free internal rotation because of weak angular anisotropy of the intermolecular bond.